ANTAMA’ RI KARAENG PANGKALANG: (Budaya ziarah makam karaeng pangkalang oleh masyarakat islam lingkungan pangkalang kel. Canrego kec. Polongbangkeng selatan Kab. Takalar) - SYAFRIWANA, SYAFRIWANA (Dahzain Nur, 2021)
Abstract This research is a descriptive qualitative research, where the writing of this journal intends to write a history or culture that is still maintained by the community until now by writing the title "Antama" Ri Karaeng Pangkalang "which means pilgrimage to the grave in this case the tomb called the Tomb of Karaeng Pangkalang. Culture is something that is commonly done by society and its development is also very fast and has become a common custom, beliefs that are believed from its predecessors such as norms, laws, rules and cultural values ??that are interrelated. Furthermore, it becomes a system and regulations that are united in the concept of culture to Arrange the social order of life in society. As is the case with pilgrimages which have various meanings, one of which is the pilgrimage to the grave which means visiting the grave with the intention of praying for the occupants of the grave and as learning material for people who make pilgrimages that one day they will be in the grave. The law regarding pilgrimage was originally forbidden, but the Prophet allowed it.